Theoretical study of inclusion complexation of 3-amino-5-nitrobenzisothiazole with β-cyclodextrin - Leila Nouar; Sakina Haiahem; Abdelaziz Bouhadiba; Fatiha Madi (My University, 2011)
The inclusion process involving β-cyclodextrin (β-CD) and 3-amino-5-nitrobenzisothiazole (ANBT) has been investigated by using the MM+ force field, AM1, PM3, HF and B3LYP theories. In this study we took into account only the stochiometry1:1. The complexation and interaction energies for both orientations considered in this research are reported. All quantum computational methods gave the A orientation as the most favorable in which the guest molecule is totally embedded in the hydrophobic cavity of the cyclodextrin with the NO2 group located near the primary hydroxyls of the β-CD and the NH2 group near the secondary hydroxyls with no hydrogen bonding formation. The negative complexation and interaction energies calculated suggest that the inclusion complexes are stable. HOMO and LUMO orbital investigations confirm the better stability of the A orientation.